Crisis in the idea of the university and its causes. Selected problems - LESZCZYŃSKI, SEWERYN (Journal of Education Culture and Society, 2020)
The article is focused on the three phenomena of the crisis in the idea of the university: the fashion of postmodernism, re-evaluation of the values, link between science and the economy. The author tried to show that these processes lead to irreversible changes in thin-king about the idea of university. The changes include social processes in the long period of time. In this way we can say that these phenomena can be considered as causes of this crisis. The author does not decide whether this is the fact. But it seems to be true. Anyway, we have to be careful in consideration of the crisis in the idea of the university: here nothing is certain. The article stays open to new ideas which may explain this topic.